Hepatic passaging of NRAS-mutant melanoma influences adhesive properties and metastatic pattern - Dietsch, Bianca; Weller, Céline; Sticht, Carsten; Torre, Carolina de la; Kramer, Martin; Goerdt, Sergij; Géraud, Cyrill; Wohlfeil, Sebastian A. (BMC cancer, 2023)
Liver metastasis is a poor prognostic factor for treatment of advanced cutaneous melanoma with either immunotherapy or targeted therapies. In this study we focused on NRAS mutated melanoma, a cohort with high unmet clinical need. WT31 melanoma was repeatedly passaged over the liver after intravenous injections five times generating the subline WT31_P5IV. The colonization of target organs, morphology, vascularization and the gene expression profiles of metastases were analyzed. After intravenous injection lung metastasis was significantly decreased and a trend towards increased liver metastasis was detected for WT31_P5IV as compared to parental WT31. Besides, the ratio of lung to liver metastases was significantly smaller. Histology of lung metastases revealed reduced proliferation of WT31_P5IV in relation to WT31 while both size and necrotic areas were unaltered. Liver metastases of both sublines showed no differences in vascularization, proliferation or necrosis. To identify tumor-intrinsic factors that altered the metastatic pattern of WT31_P5IV RNA sequencing was performed and revealed a differential regulation of pathways involved in cell adhesion. Ex vivo fluorescence imaging confirmed that initial tumor cell retention in the lungs was significantly reduced in WT31_P5IV in comparison to WT31. This study demonstrates that tumor-intrinsic properties influencing the metastatic pattern of NRAS mutated melanoma are strongly affected by hepatic passaging and the hematogenous route tumor cells take. It has implications for the clinical setting as such effects might also occur during metastatic spread or disease progression in melanoma patients.